Diplomado en Recipientes a Presión: Módulo III (Marcado y Certificación de Recipientes a Presión Conforme a la Sección VIII, Div, 1 del Código ASME) - Rivera Mendoza, Orlando R. (My University, 2007)
STAMPING DIRECTLY ON THE VESSEL WHEN CODE STAMPING IS APPLIED DIRECTLY ON THE VESSEL, STAMPING MUST: -DONE USING LETTERS AND FIGURES AT LEAST 5/16” HIGH. -BE ARRANGED PER FIGURE UG-118 WHERE SPACE PERMITS.
Keywords: Recipientes a presión; Stamping, vessel, nameplate, mode of inspection, type of construction, postweld heat treatment, removable parts, UG-90 (c) (2), inspection agreement, quality control system, renewal of code symbol stamps, manufacturer´s data reports